Notary Liability for the Sale and Purchase of PT GEI Shares Made Unlawfully (Study of Decision Number 188 PK/Pdt/2020) - Galih Wicaksono (Kosmik Hukum, 2023)
The making of the deed of sale and purchase agreement of the company's shares must follow the legal rules regulated by corporate law. However, in the making of the deed of sale and purchase of shares of PT GEI, there was a fake sale and purchase in which the procedure was carried out without the approval of the general meeting of shareholders and without payment for the sale and purchase. This research aims to analyze the legal responsibilities of notaries. This research is a normative legal research, with statutory, conceptual and case approaches. The data source used is secondary data. Qualitative normative data analysis method. Research results show that: The notary's responsibility for the fake sale and purchase of company shares is the responsibility of the civil aspect and the administrative aspect.Keywords: Responsibility Of Notary, Acts Against The Law